Transmisi pengetahuan : (satu kajian kes tentang seks dan pengetahuan tumbuhan tradisional Melayu di Kampung Bugis, Riau, Indonesia) - Achmad, Nurman (2002)
Medicinal herb is an alternative medicine for some people in society. Many studies and discussions have been done about the use of herbs and how the herb is formulated as medicine. Nevertheless, the issues about from whom and how the knowledge is passed among people in society are rarely discussed. Thus, this study examines traditional medicinal herbs, especially aboufthe use of herbs as medicines in relation to sexual activities, and how the knowledge is passed and spread to people in society.